2018
DOI: 10.1093/ajcp/aqy047
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Referral Laboratories in Rwanda

Abstract: ObjectivesWe investigated the quality system performance in Rwandan referral laboratories to determine their progress toward accreditation.MethodsWe conducted audits across five laboratories in 2017, using the Stepwise Laboratory Quality Improvement Process Towards Accreditation checklist. Laboratories were scored based on the World Health Organization grading scale (0-5 stars scale) and compared with earlier audits.ResultsBetween 2012 and 2017, only one laboratory progressed (from four to five stars). Four of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 26 publications
1
14
1
Order By: Relevance
“…Such low ratings in these services have also been reported in Ethiopia, the USA, and Saudi Arabia [ 3 , 6 , 17 , 21 ]. The physicians’ poor rating of TAT corroborates the findings of assessment done across these laboratories in 2017, which found that TAT was not regularly monitored in three out of the four laboratories [ 15 ]. Even though the targets of TAT are set, sustainable improvement would only be possible if there is regular monitoring to continuously identify and address the gaps.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Such low ratings in these services have also been reported in Ethiopia, the USA, and Saudi Arabia [ 3 , 6 , 17 , 21 ]. The physicians’ poor rating of TAT corroborates the findings of assessment done across these laboratories in 2017, which found that TAT was not regularly monitored in three out of the four laboratories [ 15 ]. Even though the targets of TAT are set, sustainable improvement would only be possible if there is regular monitoring to continuously identify and address the gaps.…”
Section: Discussionsupporting
confidence: 61%
“…Reciprocal communication and a discussion platform for stakeholders could offer a better solution for service improvement. Studies recently conducted in these laboratories also found a communication gap between laboratories and clinicians and poor performance in conducting management reviews [ 9 , 11 , 22 ]. These reviews should discuss the underlined issues, strategies, and the role of each stakeholder in a laboratory improvement program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations